Characterisation of two Plasmodium falciparum cell cycle related kinases and the effect of kinase inhibitors on the parasite - Harmse, Leonie Johanna (My University, 2008)
Abstract would not load on to DSpace.
Keywords: Plasmodium falciparum; protein kinases; kinase inhibitors